2007
DOI: 10.1021/bm061058u
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Highly Elastic Biodegradable Poly(urethane urea)

Abstract: Linear poly(urethane urea) containing a biodegradable soft segment and a hard segment built solely from methyl-2,6-diisocyanatehexanoate (LDI) is presented, using a procedure where no chain extender is required. By having LDI in excess, together with a soft segment, and adding water in the vapor phase continuously creates amines in situ resulting in hard segments containing multiple LDI units linked via urea linkages. As soft segments, polymers of trimethylene carbonate (TMC) and copolymers of TMC, epsilon-cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(71 citation statements)
references
References 32 publications
1
70
0
Order By: Relevance
“…It is postulated that the initial decrease in the $3300 cm À1 band was due to the introduction of increased polymer crosslinking by HA, causing a more rigid structure that has a decreased capacity for extensive hydrogen bonding when compared to the more flexible, linear structure of PU chains. This hypothesis of decreased hydrogen bonding is also supported by examining relative band intensity of free vs. bonded urethane carbonyls (1730 vs. 1710 cm À1 ), as described in [44,45], as this ratio showed a 5% decrease in hydrogen bonding for 0.33% PU-HA compared to PU alone. As indicated by the spectra, the 3300 cm À1 band recovered with introduction of more HA, indicating the addition of more H-bonded N-H and O-H groups.…”
Section: Synthesis and Ftirmentioning
confidence: 71%
“…It is postulated that the initial decrease in the $3300 cm À1 band was due to the introduction of increased polymer crosslinking by HA, causing a more rigid structure that has a decreased capacity for extensive hydrogen bonding when compared to the more flexible, linear structure of PU chains. This hypothesis of decreased hydrogen bonding is also supported by examining relative band intensity of free vs. bonded urethane carbonyls (1730 vs. 1710 cm À1 ), as described in [44,45], as this ratio showed a 5% decrease in hydrogen bonding for 0.33% PU-HA compared to PU alone. As indicated by the spectra, the 3300 cm À1 band recovered with introduction of more HA, indicating the addition of more H-bonded N-H and O-H groups.…”
Section: Synthesis and Ftirmentioning
confidence: 71%
“…To achieve the desired polyurethane behavior, soft segment alteration is a popular and relatively simple approach. In previous studies single component polyesters, such as PCL [14, 21, 33], poly(lactide) (PLA) [34] and poly(hydroxybutyrate) (PHB) [35]), or polycarbonates, such as poly(1,6-hexyl 1,2-ethyl carbonate) [13, 36, 37], poly(1,6-hexamethylene carbonate) [38, 39] and poly(1,3-trimethylene carbonate) (PTMC) [24, 40], in the polyurethane backbone have been shown to increase lability. For further control over degradation rate and mechanical behavior, polyester copolymers, such as PCL-PEG-PCL [22, 41], PHB containing copolymers [42, 43], and PCL-co-PLA copolymers [44] have been studied.…”
Section: Discussionmentioning
confidence: 99%
“…The polymer inherent viscosity was measured using an Ubbelohde viscometer at 22°C [24]. Each sample was dissolved in 15 mL HFIP at a concentration of 0.1 dL/100 mL and then filtered using a 0.45 μm polytetrafluoroethylene filter.…”
Section: Methodsmentioning
confidence: 99%
“…To achieve effective elastomeric properties in thermoplastic PU and PUU, soft segments modification, as an alternative, was investigated intensively. In previous studies, soft segments such as poly(!-caprolactone) (PCL) [4,5], the copolymer or blend of PCL and polylactide (PLA) [6,7], triblock PCL-PEG-PCL with poly(ethylene glycol) (PEG) as middle block [8], PCL blended with poly(1,6-hexamethylene carbonate) (PHC) [9], and the copolymer of poly(trimethylene carbonate) and PCL (PTMCco-PCL (50/50)) [10] with optimum composition and high molar mass, have shown high elongation, good flexibility and elasticity. Very few groups have addressed the effect of soft segment crystallization on polyurethane properties.…”
Section: Introductionmentioning
confidence: 99%
“…As compared to PCL, at molar mass range between 40-50 kDa, PTMC showed 30 times lower tensile strength but twice the elongation at break [14]; however, when copolymerized with other polymer such as PCL, PTMC shows better mechanical characteristics. Asplund et al [10] has recently showed that LDI-based PUU that using poly (CL-co-TMC) as soft segments achieved higher elongation than PUU that based on poly (CL-co-DLLA). In this study, we tried to lower the potential toxicity of degradation products by using the lowest amount of diisocyanate.…”
Section: Introductionmentioning
confidence: 99%